PENGARUH REVENUE SHARING DAN PEMBIAYAAN IJARAH TERDADAP PROFITABILITAS (ROA) BANK SYARIAH INDONESIA KANTOR CABANG KOTA BANDUNG PERIODE 2021-2022 - Yunus, Dede Ropik; Muhajirin, Muhajirin (An Nawawi, 2023)
This research aims to know how the influence of Revennue Sharing And Mudharabah Savingto Profitabilitas(ROA) Bank Syariah Indonesia period 2021-2022.The type of data used is secondary data. The research method used are descriptive and verification method. Data analysis using Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Coefficient Analysis and Determination, T-Test and F-Test. The results of the research show that Revenue Sharing (X1) partially has not a negativeeffect and significant against Profitabilita s(ROA), whereas Ijarah finance (X2) partially has a negative effect and not significant against Profitabilitas (ROA). Simultanously, Revenue Sharing (X1) and Pembiayaan Ijarah (X2) has a positive effect and significant against Profitabilitas (ROA) (Y). The results of the Determination Coefficient obtained the value of R square(R²) is 30,4%, while the remaining is 69,6% was influenced by other factors outside the research model.